Analysis of Compliance with Capture Fisheries Licensing in Belawan Waters at the One-stop Integrated Licensing Service and Investment Office of Sumatera Utara Province - Andayani, Cut Deby; Purwoko, Agus; Mulya, Miswar Budi (TALENTA Publisher, Universitas Sumatera Utara, 2022)
Indonesia is one of the largest maritime countries in the world. Marine resources are considered an excellent economic prospect. In the captivity fishery industry, licenses are primarily used as a controlling instrument in order to avoid overfishing. The objectives of this study are to analyze the effects of transparency, service quality, public understanding, socialization, knowledge of information technology, sanctions, and incentives on license compliance at the One-Stop Integrated Investment and Licensing Service of Sumatera Utara Province. This research employs quantitative methods by employing a multiple linear regression equation model. The purpose of this study is to examine the relationships between exogenous variables (X), namely transparency in licensing (X1), service quality (X2), public understanding (X3), socialization (X4), knowledge of information technology (X5), and sanctions and incentives (X6) against the endogenous variable (Y), which is license compliance. The result of this study shows that service quality and public understanding affect license compliance at the One-Stop Integrated Investment and Licensing Service of Sumatera Utara Province. However, licensing transparency, socialization, knowledge of information technology, applying sanctions and incentives do not affect license compliance at the One-stop Integrated Licensing Service and Investment of Sumatera Utara Province.